Peran Pamong Belajar dalam Menyelenggarakan Pembelajaran pada Peserta Didik Paket C di SKB Mojokerto - Lailatin Namiroh; Heru Siswanto (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
The purpose of this study is to show that the role of tutors in organizing learning; 1) Informer, which means providing information to students about subject matter and learning mechanisms; (2) Organizer, including academic activities such as arranging lesson schedules for the learning process, and other activities such as lesson plans; (3) Motivator, namely encouraging students to participate actively in the learning process; (4) Director, which means guiding or directing students in teaching and learning activities; (5) Innovators, meaning those who create concepts in the learning process or create learning models; (6) Disseminators, tutors have an important role as disseminators of educational wisdom and knowledge to students; (7) Facilitator, which means providing facilities that support the learning process of students; (8) Mediator, which means introducing students to learning media during the learning process; (9) Evaluation, which means conducting an assessment of students. In organizing learning at SKB Mojokerto there are obstacles in the learning process, namely the presence of students, the difficulty of tutors providing information, no access to active telephone numbers and a lack of motivation in students.